THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE ON FIRM VALUE IN SRI-KEHATI INDEXED COMPANIES - Maria Carolin Mbindi Mbira Ria; Gerianta Wirawan Yasa (Adisam Publisher, 2025)
Intense competition across various industries drives companies to continuously enhance their firm value. Firm value is an important metric for assessing performance as well as the growth prospects of a business entity, and it represents a long-term objective that companies aim to achieve. For company owners, firm value is highly important because the stock price correlates with investors’ perceptions of how successful the company’s performance is. Grounded in stakeholder theory, this study aims to examine the effect of environmental, social, and governance (ESG) disclosure on firm value in SRI-KEHATI indexed companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. This study uses leverage (DER), profitability (ROA), and industry type as control variables to reduce bias and increase research validity. The sample was determined using a purposive sampling method with the criteria of companies listed in the SRI-KEHATI index and having available ESG scores in the Refinitiv Eikon database for the 2021–2024 period. Based on these criteria, 26 companies were obtained with a total of 72 observations. Data analysis was conducted using multiple linear regression. The results show that disclosure of the environmental aspect has a negative effect on firm value, the social aspect does not show any effect on firm value, and the governance aspect is proven to have a positive effect on firm value.